Flexibility training in preadolescent female athletes: Acute and long-term effects of intermittent and continuous static stretching? - Donti, S.; Papia, K.; Toubekis, A.; Donti, A.; Sands, W. A.; Bogdanis, G. C. (Journal of Sports Sciences, 2018)
This study compared the acute and long-term effects of intermittent and continuous static stretching training on straight leg raise range of motion (ROM). Seventy-seven preadolescent female gymnasts were divided into a stretching (n = 57), and a control group (n = 20). The stretching group performed static stretching of the hip extensors of both legs, three times per week for 15 weeks. One leg performed intermittent (3 × 30 s with 30 s rest) while the other leg performed continuous stretching (90 s). ROM pre- and post-stretching was measured at baseline, on weeks 3, 6, 9, 12, 15 and after 2 weeks of detraining. ROM was increased during both intermittent and continuous stretching training, but remained unchanged in the control group. Intermittent stretching conferred a larger improvement in ROM compared to both continuous stretching and control from week 3, until the end of training, and following detraining (p = 0.045 to 0.001 and d = 0.80 to 1.41). During detraining, ROM after the intermittent protocol decreased (p = 0.001), while it was maintained after the continuous protocol (p = 0.36). Acute increases in ROM following the intermittent stretching were also larger than in the continuous (p = 0.038). Intermittent stretching was more effective than continuous, for both long-term and acute ROM enhancement in preadolescent female athletes.